Theoretical and experimental analysis of the central piles of the General Rafael Urdaneta Bridge - Sarcos Portillo, Antonio; García Legl, Hildrun (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper presents a tridimensional structural model of the original central piers of the Lake Maracaibo bridge. This model can reproduce the actual structural responses measured during experimental static load tests “in situ” with a mean error of less than 3%. The aforementioned model was obtained using the load conditions corresponding to load tests performed in 1989, taking into account the change of wires in 1981. The model is used to estimate damage in the concrete in the central piers and may be an effective tool to reproduce the actual structural responses of the central piers when subjected to any type of dynamic or static loads.